Routinizing the Use of Evidence in Policy - What is Needed?; Comment on "Sustaining Knowledge Translation Practices: A Critical Interpretive Synthesis" - Tanja Kuchenmüller; Laura dos Santos Boeira (Kerman University of Medical Sciences, 2023)
In their study of sustaining knowledge translation (KT) practices, Borst et al found that this process is an interplay of: (i) constructing and extending networks, (ii) creating contexts that support KT practices, and (iii) understanding how actors create, maintain, and disrupt institutions. Their article is an important contribution to the body of research promoting KT. In this commentary we reflect on the convergences and differences between the concepts of 'sustaining' and 'institutionalizing' KT, highlighting domains and processes related to the institutionalization, providing an analysis of KT landscape in Brazil and making a case for the need to increase countries' routine use of evidence.